Anti-Inflammatory and Antioxidant Effects of Liposoluble C60 at the Cellular, Molecular, and Whole-Animal Levels - Hui M; Jia X; Li X; Lazcano-Silveira R; Shi M (Dove Medical Press, 2023)
Mizhou Hui,1 Xiaoxiao Jia,1 Xinrong Li,2 Rayko Lazcano-Silveira,1 Ming Shi3 1College of Life Sciences, Northeast Agricultural University, Harbin, Heilongjiang, People's Republic of China; 2College of Animal Science and Technology, Qingdao Agricultural University, Qingdao, Shandong, People's Republic of China; 3Harbin Institute of Technology, Harbin, Heilongjiang, People's Republic of ChinaCorrespondence: Ming Shi, Harbin Institute of Technology, 2 Yikuang Street, Nangang District, Harbin, Heilongjiang, 150001, People's Republic of China, Tel +86 13654537645, Email shiming@hit.edu.cnIntroduction: Liposoluble carbon-60 (C60) has potential applications in many fields, including cosmetics, medical devices, and medicine, but its specific mechanism of action remains unclear. This study explored whether liposoluble C60 could be delivered to human organs, tissues, and cells through blood, extracellular fluid, and cell culture fluid and whether it exerts anti-inflammatory and antioxidant effects at the molecular, cellular, and whole-animal levels.Methods: At the cellular level, we mixed C60 dissolved in grape seed oil with cell culture medium containing 10% serum and investigated its effects on tumor necrosis factor-α (TNF-α) release, migration, phagocytosis, respiratory burst, and apoptosis in freshly isolated human neutrophils. At the molecular level, we mixed a trace amount of C60 dissolved in grape seed oil with aqueous and ethanolic solutions and studied its antioxidant effect. At the animal level, we investigated the inhibitory effect of C60 on the serum inflammatory marker C-reactive protein (CRP) in beagle dogs after oral administration of C60 dissolved in grape seed oil.Results: The results showed that the trace amount of C60 dissolved in grape seed oil significantly inhibited TNF-α release, cell migration, phagocytosis, and respiratory burst in freshly isolated human neutrophils. In addition, the trace amount of C60 dissolved in grape seed oil had a significant scavenging effect on superoxide free radicals and 1,1-diphenyl-2-trinitrophenylhydrazine free radicals. Oral administration of C60 dissolved in grape seed oil markedly reduced the level of the serum inflammatory marker CRP in beagle dogs.Conclusion: In summary, a trace amount of hydrophobic C60 in hydrophilic media effectively produced anti-inflammatory and antioxidant effects in cells and animals. C60 dissolved in grape seed oil is a novel anti-inflammatory and antioxidant drug candidate.Keywords: Carbon 60, anti-inflammation, anti-oxidation, C-reactive protein